ANALISIA PENEMPATAN LIGHTNING ARRESTER PADA CABLE HEAD 60 SEBAGAI PENGAMAN TRANSFORMATOR GIS BANDARA NGURAH RAI - I Putu Weda Jayanthana; Cok. Gede Indra Partha; I Gede Dyana Arjana (Jurnal SPEKTRUM, 2020)
The transmission line of 150 kV between GIS (Gas Insulated Switchgear) Bandara Ngurah Rai and GI Nusa Dua needs to be concerned further due to the high number of VIP customers supplied by the GIS Bandara Ngurah Rai. The location of transmission line of GIS Bandara Ngurah Rai with GI Nusa Dua is also located in the southern area of Bali in which according to the data of BMKG in 2018, it was recorded that 15.000-30.000 lightning strike occurred in the southern area of Bali. One of the devices used to protect the equipment from lightning surge is lightning arrester. Lightning arrester which is used in the network of GIS Bandara Ngurah Rai to GI Nusa Dua is placed on Cable head 60. The transmission line of GIS Bandara Ngurah Rai with GI Nusa Dua is connected by an overhead line of 8.5 km and an underground cable of 2.02 km, which is connected by terminating on Cable head 60. The distance between the Airport GIS transformer and the lightning arrester is 2.02 km, therefore it needs to be studied further in order to find out whether the protection generated by the lightning arrester has been optimal or not. The result showed that the arrester with an installation distance of 2020 meters from the transformer is still able to cut the lightning surges by producing the sparkover voltage value of 605.12 kv. Accordingly, the result of sparkover voltage exceeds the sparkover voltage of the arrester in the number of 577kv, however the voltage is still within the tolerance range of the sparkover voltage of the arrester.